Biological therapy for pyoderma gangrenosum - Krüger,Naw Ally (2013)
INTRODUCTION: pyoderma gangrenosum (PG) is a rare and severe neutrophilic dermatosis associated with inflammatory bowel disease (IBD) and other systemic diseases such as rheumatoid arthritis and hematological malignancies. Diagnosis is based on clinical criteria and exclusion of other skin disorders. There is no gold standard for the treatment of PG; traditionally intravenous corticosteroids are used, but recently the use of drugs that inhibit tumor necrosis factor alpha (TNF-alpha) has changed the management of PG, showing great effectiveness. CASE REPORT: female patient, 23 years old, diagnosed with severe nonspecific ulcerative colitis (UC) three years ago, undergoing treatment with oral mesalamine and azathioprine. She developed PG fourteen days after hospital discharge; hospitalization was due to worsening of intestinal disease symptoms. She was successfully treated using biological therapy after unfavorable evolution with corticosteroid therapy. CONCLUSION: PG, a rare extraintestinal manifestation of IBD of difficult resolution that has significant impact on patient quality of life. The use of biological therapy for PG has higher efficacy in the treatment of patients decreasing wound healing time and return to daily activities.